Interaction of Staphylococcus aureus and Acinetobacter baumannii during In Vitro β-Lactam Exposure - Smith, Nicholas M. (Antimicrob Agents Chemother, 2021)
We sought to determine if Acinetobacter baumannii is capable of altering the pharmacodynamics of an antistaphylococcal β-lactam. Two strains of methicillin-susceptible Staphylococcus aureus (MSSA) and two A. baumannii isolates were studied in 24-h static time-killing experiments under monoculture or coculture conditions. Bacterial killing of meropenem was described using an empirical pharmacokinetics/pharmacodynamics model that was developed using Hill functions. A mechanism-based pharmacodynamic model was also used to describe the effect of meropenem on each species of bacterium, interspecies interactions, and strain-based covariate effects. Monte Carlo simulations of bacterial killing effects were generated based on the population pharmacokinetics of meropenem in 2,500 simulated critically ill subjects over 48 h. Against one of the two MSSA isolates, the magnitude of bacterial killing (E(Δ)) decreased from −4.61 (95% confidence interval [CI], −5.85 to −3.38) to −2.23 (95% CI, −2.85 to −1.61) when cultured in the presence of carbapenem-resistant A. baumannii (CRAB). Similarly, the data were best described by a mechanism-based model where the number of A. baumannii cells produced a systematic increase in the S. aureus concentration for a 50% maximum killing effect (KC(50)) of 3.53-fold, thereby decreasing MSSA sensitivity to meropenem. A covariate effect by the CRAB isolate resulted in a more pronounced increase in the MSSA KC(50) for meropenem (31.8-fold increase). However, Monte Carlo simulations demonstrated that a high-intensity meropenem regimen is capable of sustained killing against both MSSA isolates despite protection from A. baumannii. Thus, A. baumannii and MSSA engage in complex interactions during β-lactam exposure, but optimal antimicrobial dosing is likely capable of killing MSSA despite the potentially beneficial interplay with A. baumannii.